Use of Dual Capillary Barrier as Cover System for a Sanitary Landfill in Singapore - Rahardjo, Harianto (2016)
Construction and demolition of buildings together with the reconstruction of roads produce a lot of solid wastes every year. These wastes create problems related to cost and space for disposal, especially for countries with limited land area like Singapore. Therefore, it is important to choose suitable landfill management system (i.e. cover system) for optimization of landfill area in Singapore. Landfill cover offers many geo-environmental benefits, including reducing water infiltration, isolating waste and controlling landfill gases. In Singapore the cover system is located within the unsaturated zone above the groundwater table. Therefore, it is necessary to incorporate unsaturated soil mechanics principles in designing the cover system for the landfill. Soil properties in the unsaturated soil zone affect the rate of wetting front movement from the ground surface. As a result, the rates of changes in pore-water pressures during and after rainfall will vary in accordance with the characteristics of unsaturated soil properties. In this study, the performance of dual capillary barrier (DCB) in minimizing rainwater infiltration into a sanitary landfill in Singapore was investigated. The DCB consists of fine recycled asphalt pavement (RAP) and coarse RAP as the materials for the fine- and coarse-grained layers, respectively. The recycled materials were used in the DCB to reduce the cost associated with the construction of a cover system in the field and to maintain environmental sustainability. Laboratory tests were conducted to characterize the index properties and hydraulic properties (i.e. soil–water characteristic curve (SWCC) and permeability function) of the RAP for the cover system under saturated and unsaturated conditions. The SWCC and permeability function were used in the finite element seepage analyses to study the effect of climate change on the soil cover system. The results from the seepage analyses show that the DCB was effective in minimizing rainwater infiltration into the sanitary landfill.